Microglia-containing neural organoids as brain microphysiological systems for long-term culture - Rittenhouse, Alex; Krall, Caroline; Plotkin, Jesse; Alam El Din, Dowlette-Mary; Kincaid, Breanne; Laird, Jason; Smirnova, Lena (Frontiers in Cellular Neuroscience, 2025)
Microglia, essential for brain development, homeostasis, and neuroinflammation, originate from the yolk sac during embryogenesis and migrate into the developing brain. Because of this developmental origin, many brain organoid models naturally lack microglia and require co-culture. To address this issue, we developed a microglia-integrated brain organoid model (immune-competent brain microphysiological system, μbMPS) by aggregating hiPSC-derived neural and microglia progenitors in U-bottom 96-well plates, allowing controlled and reproducible incorporation of microglia progenitors. We demonstrated that microglia integrated, matured, and survived long-term in the neural environment without the need for costly exogenous microglia-specific growth factors or cytokines. We maintained microglia-containing organoids for over 9 weeks, demonstrating functional activity, phagocytosis, and neuroinflammatory responses. The μbMPS also exhibited enhanced neuronal activity and maturity, providing a scalable, reproducible model for neurodevelopment, disease modeling, and neurotoxicology research.